Predicting corporate failure: evidence from Malaysian companies / Nur Azlin Ismail - Ismail, Nur Azlin (2011)
Corporate failure prediction had been widely researched especially in the UK and us. However, there is limited study on corporate failure prediction for Malaysian companies. Thus, this study aims to develop a corporate failure prediction model for Malaysian companies by examining the relationship between the accrual based and cash flow based within the same category of ratios. The categories selected for this study are liquidity, solvency, profitability and efficiency. Each category is represented by one accrual based and one cash flow based ratio. This study also examines whether there is a significant relationship between the dependent variable namely, the probability of corporate failure, and the independent variables which consist of ratios such as Current Asset to Total Asset, Operating Cash Flow Ratios, Debt Ratio, Cash Flow From Operating to Total Debt, Return on Invested Capital, Cash Return on Sales, Sales to Total Asset and Reinvestment Ratio. This study further examines the accuracy of the corporate failure prediction model by using selected ratios and logistic regression statistical was employed to construct this model. The final sample for this study consists of 25 failed companies where these companies are referred to as PN17 companies and 35 non-failed companies over a five-year period from 2005 to 2009. The finding of this study show that; a significant relationship exists between Debt ratio and Cash Flow to Debt ratio and between Return on Invested Capital and Cash Flow on Sales, all selected ratios have significant relationship with the probability of corporate failure except for Debt ratio and the logistic regression indicates that the accuracy model can be examined at an acceptable percentage